Optimization of Influential Variables in the Development of Buprenorphine and Bupivacaine Loaded Invasome for Dermal Delivery - Soraya Babaie; Arezou Taghvimi; Mohammad Charkhpour; Amir Zarebkohan; Peyman Keyhanvar; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2021)
Purpose: Hydrophilic drugs are extensively applied in clinical applications. Inadequate dermal penetration of these drugs is a great challenge. Incorporation of drugs into nano-carrier systems overcomes lower penetration drawbacks. Invasomes are novel nano-carrier systems which enhance transdermal penetration by using terpene and ethanol in their structures. buprenorphine and bupivacaine hydrochlorides are two potent analgesic drugs that are loaded simultaneously in the nano-invasome structure as opioid and non-opioid drugs. Methods: The full factorial experimental design was used for planning and estimating optimum formulations of invasome systems. Three influential factors like terpene type, terpene concentration and preparation method were comprehensively analyzed for achieving high encapsulation efficiency (EE) and optimum size. Results: The mean sizes of designed invasomes were in the range of 0.39-5.86 µm and high values of EE and loading capacity (LC) were reported as 98.77 and 19.75 for buprenorphine-loaded invasome, respectively. Zeta potential measurements confirmed that the obtained high value of EE might be as a result of reversible ionic interactions between positively charged drugs and negatively charged phospholipidic part of invasome structure. Another characterization of the prepared formulations was carried out by Fourier transform infrared (FTIR), X-ray diffraction (XRD) and dynamic light scattering (DLS) technique. Conclusion: The satisfactory obtained results of formulations encourage researchers to get optimum topical analgesic formulations with potent and rapid onset time properties required in invasive cutaneous procedures.